Model Interaksi Kepala Desa Dan Aparat di Desa Mustika Kecamatan Paguyaman Kabupaten Boalemo - Sukrianto, Sukrianto (Program Pasca Sarjana Universitas Garut, 2022)
Interaction becomes very important given that organizations have always needed information. Especially in communicating, so that in determining the effectiveness of communication within the organization depends on the achievement of organizational goals. to find out the application of the interaction model of village heads and officials in Mustika Village, Paguyaman District, Boalemo Regency. The type of research used is qualitative with a deductive approach. The data analysis technique used is Rating Scale with a quantitative approach. The result of this research is that the interaction model of the Mustika Village Head with village officials in Mustika Village in the perspective of the Leader Member Exchange is categorized as very high, indicated by 50% assessing very high, 30% assessing high, 10% assessing medium and 10% assessing low of the 7 LMX items used. in research.